Adaptasi dan Validasi Alat Ukur Perilaku Inovatif Karyawan - Iffah Rosyiana; Fendy Suhariadi; Seger Handoyo; Fajrianthi Fajrianthi (Psympathic : Jurnal Ilmiah Psikologi, 2020)
The growth of the hotel business is increasing, along with the development of tourism. This condition encourages hoteliers to compete to advance their business with a variety of service innovation processes. Therefore, it is essential to know and identify the innovative behavior of hospitality employees. This study aims to develop innovative employee behavior measurement tools. We used a quantitative study involving 143 sales marketing employees in hospitality as respondents. The sample selection uses a random sampling technique. The development of innovative behavioral questionnaires was revealed through three dimensions, namely the idea generation dimension, idea championing, and idea implementation. Data analysis used confirmatory factor analysis (CFA) with the help of Amos 22 software. The results of the study revealed that the innovative behavior measurement model met the goodness of fit criteria. These findings indicate that innovative behavior can be measured by the dimensions of idea generation, idea championing, and idea implementation. The results of this study also have implications for several hospitality practitioners to evaluate the innovative behavior of hospitality employees. Keywords: innovative behavior, scale adaptation, validity, Confirmatory Factor Analysis